Effects of US-China trade dispute on global trade relations Case study: Latin America - ÖKTEN, NİLAY (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This article is organised to summarise what has been happening in trade relations between US and China and to express how this so-called trade war affects trade relations of Latin America as a region where both actors of the dispute have been carrying a lot of trade relations in. Whether Latin America would be in advantaged position or not, as long as this trade dispute goes on between two giant economies of the world, there will be some consequences, risks and also opportunities for the region in terms of its trade relations with the parties. Therefore, it is very much fair to be interested in the region's upcoming moves and one will be able to find necessary data and information besides concluding remarks while reading this work.
Keywords: Trade dispute; Latin American trade relations; China; US; import and export; trade deficit